The identity work of Chinese charities in their online donation-oriented crowdfunding appeals. (August 2021) - Liu, Hao; Chen, Xinren
Abstract: By conceptualizing identity as a type of illocutionary resource, this study seeks to address the unheeded identity work that Chinese charities perform in their online donation-oriented crowdfunding appeals (hereafter ODC appeals). The analysis of 60 appeals drawn from an ODC platform based in China shows that via the employment of identity-oriented strategies (viz. foregrounding, creating and identification seeking), Chinese charities exploit the diverse dimensions of identity, not only of the charities themselves but of their beneficiaries and prospective donors as well. It is argued that such diverse identity work is influenced by both the institutional context surrounding ODC practices and the wider sociocultural context of China. By providing a finer picture of Chinese charities' identity work pertaining to the different dimensions of identity, this study may shed light on t he emerging research into ODC appeals and will add non-Western insights to previous discussions on humanitarian communication.